Alignment of radio galaxy axes using FIRST catalogue. Issue 1 (29th September 2020) - Panwar, Mohit; , Prabhakar; Sandhu, Pritpal Kaur; Wadadekar, Yogesh; Jain, Pankaj
ABSTRACT: We study the alignment of radio galaxy axes using the FIRST catalogue. We impose several cuts in order to select the candidates that are most likely to be free of systematic bias. In our study, we primarily focus on testing for alignment among sources within a certain angular separation from one another since for most sources redshift information is not available. We find a very significant effect for angular distances less than 1°. The distance scale of alignment is found to be roughly 28 Mpc, in agreement with earlier estimates, assuming that these sources are dominantly at redshift of 0.8. However, we are not able to entirely rule out the possibility of systematic bias in data. We also perform a full three-dimensional analysis using a smaller data sample for which redshift information is available. In this case, we only find a very weak signal at much larger distances.